Researching Posthumanizing Creativity: Expanding, Shifting, and Disrupting. (June 2022) - Chappell, Kerry
This article explores the affordances, challenges, and imperfections of researching "post"humanizing creativity, by offering two exemplars, sharing how we walk the talk, so to speak, as well as how we have been rewarded and challenged. This is all within the larger umbrella of exploring how a posthumanizing creative approach can expand pedagogical and methodological possibilities for educators, facilitators, environments, and other actants, and ultimately to see how this can disrupt established cultural and educational practice and research to address the challenges of the Anthropocene.